Financial Assets, Inflation Hedges, and Capital Utilization in Developing Countries: An Extension of McKinnon's Complementarity Hypothesis - Burkett, P.; Vogel, R. C. (Quarterly Journal of Economics, 1992)
Paul Burkett, Robert C. Vogel; Financial Assets, Inflation Hedges, and Capital Utilization in Developing Countries: An Extension of McKinnon's Complementar